2000
DOI: 10.2514/2.1116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Random Excitations on Acoustic Instabilities in Combustion Chambers

Abstract: Although ows in combustors contain considerable noise, arising from several kinds of sources, there is a sound basis for treating organized oscillations as distinct motions. That has been an essential assumption incorporated in virtually all treatments of combustion instabilities. However, certain characteristics of the organized or deterministic motions seem to have the nature of stochastic processes. For example, the amplitudes in limit cycles always exhibit a random character, and even the occurrence of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…In turbulent combustors, the thermoacoustically stable state is characterised by combustion noise, which is generated by turbulent reacting flow, has broadband characteristics, and is often assumed to be stochastic (Clavin et al, 1994;Burnley & Culick, 2000;Lieuwen, 2002). Lieuwen & Banaszuk (2005) consider noise to be forcing of the dynamical system (additive noise) or fluctuation of the system's parameters (parametric noise).…”
Section: Stochastic Approachmentioning
confidence: 99%
“…In turbulent combustors, the thermoacoustically stable state is characterised by combustion noise, which is generated by turbulent reacting flow, has broadband characteristics, and is often assumed to be stochastic (Clavin et al, 1994;Burnley & Culick, 2000;Lieuwen, 2002). Lieuwen & Banaszuk (2005) consider noise to be forcing of the dynamical system (additive noise) or fluctuation of the system's parameters (parametric noise).…”
Section: Stochastic Approachmentioning
confidence: 99%
“…The total acoustic power P ac emitted from a turbulent reacting jet can be estimated as (19) and the rate at which chemical and kinetic energy are supplied to the jet can be computed from…”
Section: Far-field Approximation and Acoustic Powermentioning
confidence: 99%
“…In this respect, the broadband acoustic perturbations interact only weakly with the heat release rate, so that this process is often considered to be passive [17]. However, theoretical analyses showed that noise in enclosed combustion systems, for instance in gas turbines and advanced low-emission aircraft engines [6], plays a critical role as precursor for combustion instabilities [18,19], and even such weak interactions can trigger thermoacoustic instabilities, in which the flame becomes an active part of the acoustic system [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Although dependent on engine configuration and operating regime, these direct core noise contributions typically fall in the low-frequency range, corresponding to the 200-400 Hz frequency band. 16,17 In this context it is also noted that these direct noise-sources can act as a bypass mechanism to excite thermo-acoustic instabilities in the combustor, [18][19][20][21] and even relatively weak interactions can trigger combustion instabilities. 22 Apart from combustion-generated pressure perturbations, the unsteady combustion process generates velocity and entropy fluctuations that exit the combustor, and are convected to the nozzle.…”
Section: Precursors For Instabilitiesmentioning
confidence: 99%